Dechema chemistry data series : thermal conductivity and viscosity data of fluid mixtures 1 tables, diagrams, correlations and literature survey - Stephan, K.; Heckenberger, T. (Dechema Frankfurt, 1988)
part 1
Keywords: Fluid mixtures; Thermal conductivity